Identification of metabolites for biomarker of nitrogen and potassium use efficiency in oil palm - Setiowati, Retno Diah; Sri Wening; Nuringtyas, Tri Rini; Rahayu, Megayani Sri; Sudarsono, Sudarsono (Menara Perkebunan, 2025)
Nutrient-use efficiency in oil palm is important for economic and environmental reasons. This research aimed to identify biomarkers to discriminate between tolerant and susceptible oil palms to potassium (K) and nitrogen (N) deficiency. A screening of oil palm materials for N or K use efficiency was conducted using an omission trial experiment, where only targeted nutrient was applied as treatment, while all other nutrients were applied as recommended. The treatment was performed in the main nursery for ten months to identify progenies with contrasting traits. Metabolite analysis was performed to identify specific metabolites as biomarkers for N-efficient and K-efficient palms. Samples taken from the roots of the contrasting progenies were treated with liquid nitrogen prior to grinding into a powder for liquid chromatography-high resolution mass spectrometry (LC-HRMS) analysis. The LC-HRMS analysis showed 277 metabolites from K and N treatments after data trimming, which were then analysed in MetaboAnalyst 6.0 for biomarker identification. The results showed that some metabolites were statistically significant. Metabolites identified in more than one analysis have a higher likelihood of being considered as biomarkers. In this experiment, we compared PLS-DA, sPLS-DA, and Random Forest. However, some identified metabolites were not to occur naturally in the treatment palms. Some amino acids and antioxidants were promising biomarkers to differentiate the N-deficiency-tolerant and K-deficiency-tolerant palms. Thus, the biomarkers facilitate the breeding scheme to create a nutrient-efficient palm planting material.